Renal Impairment and Prognosis of Patients with Atrial Fibrillation Undergoing Coronary Intervention - The AFCAS Trial. - Heli M Lahtela; Tuomas O Kiviniemi; Marja K Puurunen; Axel Schlitt; Andrea Rubboli; Antti Ylitalo; José Valencia; Gregory Y H Lip; K E Juhani Airaksinen (PLoS ONE, 2015)
Renal impairment is a well-known risk factor for cardiovascular complications, but the effect of different stages of renal impairment on thrombotic/thromboembolic and bleeding complications in patients with atrial fibrillation (AF) undergoing percutaneous coronary intervention (PCI) remains largely unknown. We sought to evaluate the incidence and clinical impact of four stages of renal impairment in patients with AF undergoing PCI.We assessed renal function by estimated glomerular filtration rate (eGFR) and outcomes in 781 AF patients undergoing PCI by using the data from a prospective European multicenter registry. End-points included all-cause mortality, major adverse cardiac and cerebrovascular events (MACCE) and bleeding events at 12 months.A total of 195 (25%) patients had normal renal function (eGFR ≥90 mL/min), 290 (37%) mild renal impairment (eGFR 60-89), 263 (34%) moderate renal impairment (eGFR 30-59) and 33 (4%) severe renal impairment (eGFR <30). Degree of renal impairment remained an independent predictor of mortality and MACCE in an adjusted a Cox regression model. Even patients with mild renal impairment had a higher risk of all-cause mortality (HR 2.25, 95%CI 1.02-4.98, p=0.04) and borderline risk for MACCE (HR 1.56, 95%CI 0.98- 2.50, p=0.06) compared to those with normal renal function.Renal impairment is common in patients with AF undergoing PCI and even mild renal impairment has an adverse prognostic effect in these patients requiring multiple antithrombotic medications.